2022
DOI: 10.51559/pedscij.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of centella asiatica extract in Zebrafish (Danio rerio) larvae as a Chronic Constant Hypoxia (CCH) model

Abstract: Backgound: Chronic Constan Hypoxia (CCH) are able to occur in cyanotic congenital heart disease and bronchopulmonary dysplasia (BPD). Centella asiatica has antioxidant and neuroprotective effects in experimental animals.This study aims to observe the effect of Centella asiatica ethanol extract on Zebrafish in chronic hypoxic conditions Method: A laboratory experimental study with a randomized post-test controlled group design was conducted among 20 Zebrafish (Danio rerio) 3-8 day post fertilization (dpf)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…CA was previously reported to have antioxidant properties and protect rotenone-induced zebrafish embryos from oxidative stress ( Cory’ah et al , 2020 ). A previous study demonstrated that CA extracts at concentrations of 1.25–5 μg/ml could enhance body length and locomotor activity in zebrafish larvae in the chronic constant hypoxia model ( Ariani and Widiyastuti, 2022 ). The bioactive compounds from CA include triterpenoids, phenolic compounds, essential oils, pectins, free amino acids, vitamins, and minerals ( Tripathy and Srivastav, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…CA was previously reported to have antioxidant properties and protect rotenone-induced zebrafish embryos from oxidative stress ( Cory’ah et al , 2020 ). A previous study demonstrated that CA extracts at concentrations of 1.25–5 μg/ml could enhance body length and locomotor activity in zebrafish larvae in the chronic constant hypoxia model ( Ariani and Widiyastuti, 2022 ). The bioactive compounds from CA include triterpenoids, phenolic compounds, essential oils, pectins, free amino acids, vitamins, and minerals ( Tripathy and Srivastav, 2023 ).…”
Section: Introductionmentioning
confidence: 99%